Chemical Constituents and Energy Content of Cryptostegia grandiflora: A Promising Multi-Use Crop - Augustus, G.D.P.S.; Rajarathinam, K.; Shanthakumari†, G.D.; Kanan, D.; Jayabalan, M. (Asian Journal of Chemistry, 2016)
Cryptostegia grandiflora, a member of Asclepiadaceae, was evaluated as a source of multiuse crop. The plant contained 14.0 protein, 6.5 oil, 6.9 polyphenol and 2.13% hydrocarbon. The gross heat value of the plant sample was 3878.0 cal/g; oil fraction was 7350.1 cal/g; hydrocarbon fraction was 9300.0 cal/g. The NMR spectrum of the hydrocarbon fraction reveals the presence of cis-polyisoprene system. The oil fraction constitutes both saturated and unsaturated fatty acids with the constituents of lauric acid (trace), myristic acid (trace), palmitic acid (5.7%), arachidic acid (6.1%), oleic acid (22.4%), linoleic acid (20.9%) and linolenic acid (30.6%). The plausible reactive oxygen species (ROS) producing compounds in the polyphenol fraction is further warranted for studying in treating cancerous tissue using laser lie photo-dynamic therapy (PDT).